A Balancing Pretence: The Johnson Administration's Policy towards Jordan, 1964–1967. Issue 3 (27th May 2018) - Aalmen Markussen, Joakim; Waage, Hilde Henriksen
Abstract: King Hussein of Jordan was often at odds with his less conciliatory counterparts in the Arab world. He was one of the few Arab leaders who engaged and communicated with Israel. The administration of US President Lyndon B. Johnson wanted to ensure the continuation of Hussein's moderate line towards Israel and sold weapons to Jordan. However, providing military support to an Arab state when the vast majority of Americans favoured Israel involved significant political costs. As the Johnson administration saw it, openly favouring only Israel would negatively affect the USA's position and interests in the Arab world. Therefore, Johnson pursued a policy of seemingly balancing Israeli and Jordanian interests. This article argues that the USA supported Jordan primarily to ensure Israel's security, but ultimately, the Johnson administration lacked the will and understanding to properly address Jordan's concerns and failed to prevent King Hussein from joining the Arab side of the 1967 War against Israel.